National park science a century of research in South Africa - Carruthers, Jane (Ecology, biodiversity and conservation, 2017)
South Africa is renowned for its wildlife and environmental conservation in iconic national parks such as the Kruger, one of the world's first formal protected areas. However, this is the first book to thoroughly analyse and explain the interesting and changing scientific research that has been accomplished in South Africa's national parks during the twentieth century. Providing a fascinating and thorough historical narrative based on an extensive range of sources, this text details the evolution of traditional natural history pursuits to modern conservation science in South Africa, covering all research areas of conservation biology and all the national parks around the country. It reveals the interaction between the international context, government, learning institutions and the public that has shaped the present conservation arena. A complex story that will interest and inform not only those involved in conservation science of South Africa, but worldwide